A study on sheep farming practices in relation to future production strategies in Bensa district of southern Ethiopia - Kenfo, H.; Mekasha, Yoseph; Tadesse, Y. (Springer, 2018)
The study was carried out in Bensa district of Sidama zone, Southern Ethiopia. Agro-ecologically, the study sites were classified into highland and mid-altitude. The objective of the study was to identify sheep farming practices in relation to future production strategies in the study area. A total of 128 households from four kebeles (lower administrative structure) were selected purposively based on sheep population and production potential and accessibility. Data was collected through semi-structured questionnaire, focus group discussions, and key informants. The result showed that most of the household heads were male (92.75%) and mixed crop-livestock system was the dominant production system. Among the livestock species, sheep accounted for the largest proportion across the two agro ecologies and the average sheep flock size/household was 4.6 ± 0.33 and 22 4.3 ± 0.213 in highland and in mid-altitude, respectively. The primary reason of keeping sheep was for cash income and saving across the two agro ecologies. The major feed resources for sheep during the wet and dry seasons were natural pasture and crop residues respectively across the two agro ecologies. Feed shortages, disease, parasite prevalence, and market were the major sheep production constraints in highland while feed shortage, genotype, disease, parasite prevalence, and market in mid-altitude. It can be concluded that for enhancing future production from sheep in the area, emphasis is to be given on feed availability, disease management, breeding policy, and marketing strategies.